Adsorpsi Logam Cd Menggunakan Î±-Selulosa dari Kulit Buah Nanas - Mandasari, Weni; Sitorus, Berlian; Rudiyansyah, Rudiyansyah (Universitas Tanjungpura, 2023)
Pineapple fruit is widely consumed that impact on the waste produced. One of which is pineapple peel has a high cellulose content of around 69.5-71%. In this research, the synthesis of Î±-cellulose from pineapple peel was tings in order produce an adsorbent for Cd2+ metal ions. The prepared pineapple peel powder was delignified using 2% NaOH to remove lignin, were delignified again using 18% NaOH. The Î±-cellulose formed was bleached using 3.5% NaOCl. Î±-cellulose was hydrolyzed using H2SO4 with various concentrations of 2, 3 and 4%. The goal is to determine the optimum absorption of the adsorbent. Based on this research, it was found that the maximum adsorption capacity was obtained at 4% H2SO4 variation which is 108 mg/g and an efficiency of 54%. The adsorption isotherm model on cellulose meets the assumptions of chemical, and physical adsorption as shown by the R2 value of 0.999. Chemical adsorption (Langmuir isotherm) is indicated by the reaction of the OH group with the metal ion Cd2+. Physical adsorption (Freundlich isotherm) that occurs at heterogeneous adsorption sites supported by changes in surface area (BET) values.